Physical and physiological characteristics of the high performance orienteers (Agora for Physical Education and Sport, 2020)
In the sport of orienteering, due to the lack of specific studies about performance analysis, it is needed to draw on high level orienteers data. This paper, even recognizing the psychological importance in competition success, aims to collect physical and physiological data which define this select group of athletes.
Keywords: orienteering; maximal oxygen consumption; anaerobic threshold; anthropometry